The Brexit challenge for Ireland and the United Kingdom : constitutions under pressure - Doyle, Oran; McHarg, Aileen; Murkens, Jo Eric (Cambridge : Cambridge University Press, 2021)
Since the 1950s, European integration has included ever more countries with ever-softening borders between them. In its apparent reversal of integration and its recreation of borders, Brexit intensifies deep-seated tensions, both institutional and territorial, within and between the constitutional orders of the United Kingdom and Ireland. In this book, leading scholars from the UK and Ireland assess the pressures exerted by Brexit, from legal, historical, and political perspectives. This book explores the territorial pressures within the UK constitution, connecting them to the status of Northern Ireland before exploring how analogous territorial pressures might be addressed in a united Ireland. The book also critically analyses the Brexit process within the UK, drawing on Irish comparative examples, to assess unresolved tensions between popular mandate, legislative democracy, and executive responsibility. Through practical application, this book explores how constitutions function under the most intense political pressures.
Introduction : the constitutional tensions of Brexit / Oran Doyle, Aileen McHarg, Jo Murkens -- Subsidiarity, competence, and the UK territorial constitution / Jo Hunt -- Brexit and the mechanisms for the resolution of conflicts in the context of devolution : do we need a new model? / Elisenda Casanas Adam -- Beyond matryoshka governance in the 21st century : the curious case of Northern Ireland / Sylvia de Mars, Aoife O'Donoghue -- Political parties in Northern Ireland and the post-Brexit constitutional debate / David Mitchell -- The constitutional significance of the people of Northern Ireland / C. R. G. Murray -- The constitutional politics of a United Ireland / Oran Doyle, David Kenny, Christopher McCrudden -- The minority rights implications of Irish unification / James Rooney -- Populism and popular sovereignty in the UK and Irish constitutional orders / Eoin Daly -- Party, democracy, and representation : the political consequences of Brexit / Malcolm Petrie -- Westminster versus Whitehall : what the Brexit debate revealed about an unresolved conflict at the heart of the British Constitution / David Howarth -- Brexit and the problem with delegated legislation / Adam Tucker -- Litigating Brexit / Christopher McCorkindale, Aileen McHarg -- The law officers : the relationship between executive lawyers and executive power in Ireland and the United Kingdom / Conor Casey -- In search of the constitution / Martin Loughlin.
Title from publisher's bibliographic system (viewed on 20 Aug 2021).
Keywords: European Union -- Great Britain; European Union -- Ireland; Constitutional law -- Great Britain; International and municipal law -- Ireland; International and municipal law -- Great Britain; Constitutional law -- Ireland; Great Britain -- Foreign relations -- Ireland; European Union countries -- Economic integration; Ireland -- Foreign relations -- Great Britain